Nanomaterial-based drug delivery carriers for cancer therapy - Feng, Tao; Zhao, Yanli (Routledge, Taylor and Francis Group, 2017)
This brief summarizes different types of organic and inorganic nanomaterials for drug delivery in cancer therapy. It highlights that precisely designed nanomaterials will be the next-generation therapeutic agents for cancer treatment.
Keywords: Antineoplastic agents.; Drug carriers (Pharmacy); elektronické knihy; electronic books